Remittance: Role and Challenges in Nepalese Economy - Budhathoki, Krishnahari (Economic Journal of Nepal, 2017)
Both developing and developed countries have made a significant study of remittance and labor migration. Developing countries have attained benefits from remittance to uplift economic activities like maintaining household consumption, increasing pattern of saving and investment, receiving foreign currencies for imports, making favorable balance of payments, diplomatic activities, enhancing social and infrastructural development and maintain macroeconomic stability. The study explores the role and challenges of remittance in Nepalese economy. No doubt, Nepal as least developing country attains lots of benefits from remittance and labor migration. Along with such economic and social benefits, remittance generates a lot challenges in economy such as brain drain, trade deficit, shortage of man power, higher labor cost, backwardness of productive sectors of economy and a lot of social problems. The study also points out of effective use of remittance that helps to mobilize internal resource to create employment opportunities in a country with a formulation of proper implementation of necessary policy regarding a proper utilization of remittance.